CORRELATION BETWEEN FARMER BEHAVIOR WITH THE SUCCESS OF BROILER FARMING BUSSINESS IN EAST SUMBA REGENCY - N. A. M., Pricilia,; Suparta, I N.; Tatik Inggriati, N. W. (Jurnal Peternakan Tropika, 2019)
Broiler farms in East Sumba Regency are spread throughout the region with small-scale businesses, namely 100-12,000 head/farmer. However, business conditions are not sufficient to achieve an optimum success of the farm business. However, conditions are not perfect to achieve optimal job success. The purpose of this study was to: 1) farmer behavior about the management of broiler business; 2) the nature of the correlation with breeders in the race chicken breeding business; 3) correlation between motivation and behavior; and 4) correlation between breeders' behavior and business performance of broiler chickens. The amount of income is 70 farmers. The research sample was taken using the "Quota Purposive Sampling" method, which was 41 farmers. The type of data used is primary data and secondary data. Primary data obtained from direct interviews and secondary data data obtained from literature studies. Analysis which is a descriptive analysis and Spearman level analysis. The results of the study showed that, the behavior of farmers about management of broiler farm business was in the good category with an average percentage of achieving score is 69,83%, knowledge have low category (50,97%), attitude categorized as very positive (94,63%) and moderate categorical skill (63,90%). Education level, number of personality and personality that has a positive correlation with farmer behavior (P<0,10) and farmers' motivation is included in the strong category (68,24%). In addition, motivation has a real positive correlation (P<0,05) with farmer behavior. Farmer behavior has a very real positive correlation with farmer achievement (P<0,01). Keywords: Farming, Broiler, Behavior, Success